Evaluating psychological distress in Chinese patients with head and neck squamous cell carcinoma planned for radiotherapy: a cross-sectional study using the distress thermometer - Chenjing Zhu; Qingjuan Chen; Wei Du; Hanzi Xu; Xia He (BMC Psychology)
Abstract Objective We aim to estimate the prevalence of baseline clinically significant distress in Chinese patients with head and neck squamous cell carcinoma (HNSCC) before receiving the first radiotherapy and assess factors predictive of distress. Methods One hundred and sixty-eight patients were enrolled to complete a set of questionnaires including Distress Thermometer (DT) and Hospital Anxiety and Depression Scale (HADS). Of these, 131 questionnaires were available for the final analysis. The accuracy of DT was validated using HADS as the gold standard, and receiver operating characteristic (ROC) curves were employed to identify the optimal cutoff score of DT. Results Distress was reported in sixty-two patients (47%). Patients who were visited in the last week (p = 0.022) and those with medical-related occupations (p = 0.017) were less likely to suffer from psychological distress. Additionally, religious belief was negatively associated with both the DT and HADS-T scores, indicating that patients with religious beliefs were less likely to report high levels of distress (odds ratio (OR) for DT ≥ 4 = 0.291, p = 0.039; OR for HADS-T ≥ 15 = 0.316, p = 0.047). Factors such as age, gender, marital status, education and residency did not contribute to distress levels. DT was significantly correlated with HADS-T (Correlation coefficient (r) = 0.624, p < 0.001) and the best cutoff score of DT was 4 in screening distress. Conclusions DT was a brief and effective tool to screen distress among HNSCC patients.